2021
DOI: 10.3389/fendo.2021.671126
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Significantly Decreased Serum Circulating Mesencephalic Astrocyte-Derived Neurotrophic Factor Level With an Increased Risk of Future Cardiovascular Disease in Adult Patients With Growth Hormone Deficiency

Abstract: ObjectiveAdult growth hormone deficiency (AGHD) is a rare chronic inflammatory disease caused by damage to the pituitary gland and is accompanied by disorders of multiple metabolic pathways. By examining the correlation between the serum mesencephalic astrocyte-derived neurotrophic factor (MANF) levels of AGHD patients and those of normal controls, we hope to elucidate the close relationship among MANF, lipid metabolism and insulin resistance in AGHD and discuss the potential therapeutic value of MANF.MethodsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
3
1
Order By: Relevance
“…Although several authors associate GHD in adults with insulin resistance, this association is not well established in the literature. Conversely, a recent study has shown that adult patients with GHD are more sensitive to insulin than the control group matched for age, sex, and BMI through HOMA-IR [22,23]. In our study, using the HEC, we found no differences in SI between patients with AOGHD and the matched control group.…”
Section: Discussioncontrasting
confidence: 90%
“…Although several authors associate GHD in adults with insulin resistance, this association is not well established in the literature. Conversely, a recent study has shown that adult patients with GHD are more sensitive to insulin than the control group matched for age, sex, and BMI through HOMA-IR [22,23]. In our study, using the HEC, we found no differences in SI between patients with AOGHD and the matched control group.…”
Section: Discussioncontrasting
confidence: 90%
“…In healthy adults, lower levels of IGF-1 were associated with lower fasting blood glucose, insulin and C-peptide levels 27 . Previous studies have revealed that diabetes is a common comorbidity in AGHD and is a major contributor to cardiovascular risk 28 . In our study, fasting blood glucose was also remarkably elevated in AO AGHD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the serum, MANF levels are increased in conditions such as ischemic stroke, drug-induced liver injury, hyperlipidemia, obesity, and types 1 and 2 diabetes (53,61,64,66,69,73). In contrast, decreased levels of MANF in the serum have been reported in adult patients with growth hormone deficiency, major depressive disorder, nonalcoholic steatohepatitis, and polycystic ovary syndrome (56,62,68,70). Expression of CDNF has been investigated in different disease conditions, but not as extensively as MANF.…”
Section: Cdnf and Manf Expression In Human Diseasesmentioning
confidence: 99%